Ladder drill portable: Agility tools for sports - Wijayanti, Ni Putu Nita; Saputro, Deny Pradana; AF, Oca Fernandes; Febri, Raja (Journal Sport Area, 2021)
The development of portable ladder drills as a medium for agility training has never been touched once. The ladder drill tool's mobile concept will make it easier for the trainer to use the device with a variety of varied agility training movements and can be used in more sports. Based on this, the research is carried out in an effort to make portable ladder drill training media that is useful as a medium for agility training. This research uses research and development level 3 methods. Product trials are conducted in three types, that is one on one practices with four respondents, small group trials worked with five respondents athletes, students majoring in Sports Education FKIP Universitas Riau, and large-scale tests. They work on 11 athletes KONI and Dispora Riau Province. The data analysis technique used in this research is the quantitative descriptive analysis technique. Furthermore, data collection techniques use a questionnaire (questionnaire). The results of this study indicate that: assessments made by material experts, media experts, one-on-one trials, small-scale trials, and large-scale trials are above 83 percent. Based on this study results, it can be concluded that the development of portable ladder drills is declared feasible as a medium to increase agility by sports actors. Considering that this development still has shortcomings, future research recommendations are related to providing cheaper and more functional product materials in terms of equipment installation efficiency.